2011
DOI: 10.1186/1752-4458-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Youth mental health first aid: a description of the program and an initial evaluation

Abstract: BackgroundAdolescence is the peak age of onset for mental illness, with half of all people who will ever have a mental illness experiencing their first episode prior to 18 years of age. Early onset of mental illness is a significant predictor for future episodes. However, adolescents and young adults are less likely than the population as a whole to either seek or receive treatment for a mental illness. The knowledge and attitudes of the adults in an adolescent's life may affect whether or not help is sought, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 25 publications
5
127
0
2
Order By: Relevance
“…Thus, in contrast to most school mental health interventions, 22,[48][49][50] the application of The Guide builds on existing classroom teaching processes and does not require additional investment in the purchase and application of standalone programs that have not been specifically created to be contextually integrated into school settings. 47,51,52 Of added specific interest, our study and others identified above have demonstrated that simply applying an MHL resource (The Guide) integrated into usual school curriculum demonstrates a highly positive impact on decreasing stigma in students pertaining to mental health and mental illness. This allows for schools to consider an alternative approach to stigma reduction than those that are often applied as standalone interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in contrast to most school mental health interventions, 22,[48][49][50] the application of The Guide builds on existing classroom teaching processes and does not require additional investment in the purchase and application of standalone programs that have not been specifically created to be contextually integrated into school settings. 47,51,52 Of added specific interest, our study and others identified above have demonstrated that simply applying an MHL resource (The Guide) integrated into usual school curriculum demonstrates a highly positive impact on decreasing stigma in students pertaining to mental health and mental illness. This allows for schools to consider an alternative approach to stigma reduction than those that are often applied as standalone interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our findings indicate that health or mental health professionals are the third most common source of parent mental health information per provider reports. Given parents' reliance on informal sources of support, communities and workplaces could benefit from continued trainings from sources such as Mental Health First Aid and Youth Mental Health First Aid (Kelly et al, 2011;Kitchener & Jorm, 2006) to prepare informal sources to assist and respond to parental concerns regarding their children's mental health. In addition, because first-line, generalist professionals such as family practitioners and nurses are frequently relied upon by parents for mental health information and assistance , continued efforts to provide mental health education to those professionals is needed as well.…”
Section: Implications Of Providers' Perceptions For Increasing Parentmentioning
confidence: 99%
“…(60). Adults trained in PFA report increased knowledge, skills, and self-efficacy in applying skills to support youth with histories of trauma (61,62). One study also reported PFA being effective in improving connectedness and stress among youth traumatized by a disaster, bullying, death or illness of a family member, or injury (59).…”
Section: Approaches To Reducing the Burden Of Acesmentioning
confidence: 99%